IMPLEMENTASI MUDARABAH PADA LEMBAGA KEUANGAN SYARIAH - Muhammad Hatta (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The problems studied in this study are related to the implementation of Muḍārabah according to the Sharia Economic Law Compilation (KHES) and the Muḍārabah mechanism at Bank Syariah Indonesia Wonomulyo. This type of research is a qualitative research that builds meaning based on data obtained from the field. The procedure for this qualitative research is to process data which will produce descriptive data in the form of written and spoken words from people and observable behavior. Data was collected by conducting observations, in-depth interviews and documentation. Data analysis is done by giving meaning to the data that has been collected, then from the data a conclusion is drawn. The results of this study reveal that the implementation of muḍārabah in Islamic financial institutions, namely Bank Syariah Indonesia Wonomulyoakad muḍārabah has fulfilled and is in accordance with Islamic law and is contained in the Sharia Economic Law Compilation (KHES). At BSI KCP Wonomulyo, the application of muḍārabah contracts is only for collecting funds from customers, namely muārabah savings and muḍārabah deposits in distributing funds not being used. This is because the amount of risk that will be accepted by the BSI bank must bear all the losses experienced by the customer as a capital manager. Then the profit sharing or the ratio received must be based on an agreement between the two parties and will be received every month and within a predetermined period of time. REFERENCES Al-Qur’an al-Karim Abbas, A. (2019). Analisis Laporan Keuangan Perbankan Syariah. Aguspian. (2012). Analisis Pembiayaan Mudharabah Terhadap Tingkat Profitabilitas (Profit Margin) Pada PT. Bank Sulselbar Cabang Syariah Makassar. Skripsi sarjana: Jurusan Manajemen: UIN Alauddin Makassar. Ahmadi, Bagus. “Akad Bay’, Ijarah Dan Wadi’ah Perspektif Kompilasi Hukum Ekonomi Syariah (KHES)” dalam http://ejournal.iain-tulungagung.ac.id/index.php/epis/ article/view/28, (diakses pada tanggal 27 Agustus 2021, jam 09.30). Al-faifi, Sulaiman. (2010). Mukhtashar Fiqih Sunnah Sayyid Sabiq. Solo: PT Aqwam Media Profetika. Ambarukmi, Indri. (2018). Pengaruh Pembiayaan Mudharabah Terhadap Pendapatan Bagi Hasil Bank, (Skripsi Sarjana: Jurusan Perbankan Syariah: UIN Raden Intan Lampung, Asrullah, (2016). Implementasi Tabungan Mudharabah pada PT Bank Muamalat Indonesia Cabang Pembantu Parepare” (Skripsi Sarjana: Jurusan Syariah dan Ekonomi Islam: Parepare Departemen Pendidikan Nasional. (2008). Kamus Besar Bahasa Indonesia, Edisi IV (cet. I; Jakarta: Gramedia Pusaka Utama Direktorat Perbankan Syariah Bank Indonesia, “Kodifikasi Produk Bank Syariah” Hayati, Alifudin. (2018). Tinjauan Hukum Islam Terhadap Implementasi Akad Mudharabah, Semarang. Ibrahim, Khudari. (2014). Penerapan Prinsip Mudharabah Dalam Perbankan Syariah, Jurnal IUS (Kajian Hukum dan Keadilan) Vol II. Idul Muhammad. (2018). Implementasi Akad Mudharabah Pada Produk Deposito Di Bank Sulselbar Kantor Layanan Syariah Cabang Parepare. Skripsi Sarjana: Jurusan Syariah dan Ekonomi Islam: IAIN Parepare. Irfan. (2018). Analisis Pembiayaan Mudharabah Perbankan Syariah Di Indonesia Lhoksumawe: Unimal Press Ismail. (2017). Perbankan Syariah. Jakarta: Kencana Kementerian Agama RI. (2019). Al-Qur’an Al-Karim dan Terjemahan Bahasa Indonesia dan Bahasa Mandar. Jakarta: Bintang Indonesia. Mahkamah Agung RI. (2008). Kompilasi Hukum Ekonomi Syariah, Jakarta. Masse, R. A.( 2010). Konsep Mudharabah Antara Kajian Fiqh dan Penerapan Perbankan, Jurnal Hukum Diktum, 8 Nomor 1 Januari. Mughits, Abdul. (2019). Kompilasi Hukum Ekonomi Islam (KHES) dalam Tinjauan Hukum Islam” dalam https://journal.uii.ac.id/index.php/JHI/article/viewFile/151/116. Muhammad bin Muhammad al-Mukhtar al-Syanqiti,Syarh Zad al- Mustaqna’li al-Syanqiti. Digital Library, al-Makhtabah al-Syamilah al-Isdar al-Sani,2005. Mustofa, Imam. (2016). Fikih Muamalah Kontemporer. Jakarta:PT RajaGrafindo Persada. Nasution,Khairuin. (2009). Pengantar Studi Islam. Yogyakarta: ACAdeMIA dan TAZZAFA. Nisa’, Khairun.  (2019). Implementasi Kompilasi Hukum Ekonomi Syariah Dalam pembiayaan Mudharabah Di BMT Surya Kencana Bolong Ponorogo.Skripsi Sarjana: Jurusan Ekonomi Syariah. IAIN Ponorogo. Otoritas Jasa Keuangan. (2019). Standar Produk mudharabah. Sabiq, Sayyid.  (2006). Fikih Sunnah. Jakarta: Pene Pundi Angkara. Sugiyono. (2015). Metode Penelitian Pendidikan. Bandung:cet.2. Perpustakaan Nasional, Kompilasi Hukum Ekonomi Syariah Putri, Tiara Nerisa. (2017). Penerapan Akad Mudharabah Di KSPS BTM Al-Amin Ditinjau dari Hukum Ekonomi Syari’ah. Metro:Tidak ada Penerbit 2017. Undang-Undang No. 3 Tahun 2006 Undang-Undang Republik Indonesia Nomor 19 Tahun 1998 Undang-Undang RI Nomor 39 tahun 2006 Yunus, Mahmud. Kamus Arab Indonesia. Jakarta: PT. Mahmud Yunus Wa Dzurriyah.